Evaluasi Efektivitas Penggunaan Telehealth dalam Meningkatkan Kemampuan Perawatan diri dan Kontrol Glikemik pada Pasien Diabetes Mellitus : Narrative Review - falah, fakhriatul (Jurnal Teknologi informasi dan Ilmu Komputer, 2025)
Diabetes is a disease characterized by elevated blood glucose levels, known as hyperglycemia. Poor self-care skills in diabetes patients result in uncontrolled blood sugar and various complications. To address this, educational and counseling strategies are implemented for both diabetes patients and their families through telehealth. The purpose of this study was to evaluate the effectiveness of using various telehealth media in improving self-care behavior and glycemic control in diabetes patients. This study was conducted using a literature review method using a comparative experimental design through a randomized controlled trial method. Based on a systematic analysis of 18 articles, it was found that telemedicine can be used as an effective educational medium to improve self-care skills in diabetes patients and improve glycemic control in patients by reducing blood glucose and HbA1C levels.